2006
DOI: 10.1039/b601971d
|View full text |Cite
|
Sign up to set email alerts
|

UV-B light induces an adaptive response to UV-C exposure via photoreactivation activity in Euglena gracilis

Abstract: Phytoplankton such as Euglena are constantly exposed to solar light which is used for photosynthesis. Although the solar ultraviolet (UV) induces DNA damage such as cyclobutane-pyrimidine dimers (CPDs), many kinds of living organisms can repair CPDs by photoreactivation (PR) utilizing the near-UV/blue light component in sunlight. Euglena cells are known to possess such PR activity. In the present paper, the formation of CPDs induced by UV-C exposure and the photoreactivation PR repair of these CPDs by UV-A are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Euglena is highly adaptable to changing environments, some adverse stresses like UVB (Takahashi et al, 2006 ), heavy metals (Moreno-Sánchez et al, 2017 ), and antibiotics (Ebringer, 1964 ). In this study, microalgal cells showed tolerance to antibiotics, PRM, without significant cell growth inhibition, chlorophyll reduction, and paramylon and lipid alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Euglena is highly adaptable to changing environments, some adverse stresses like UVB (Takahashi et al, 2006 ), heavy metals (Moreno-Sánchez et al, 2017 ), and antibiotics (Ebringer, 1964 ). In this study, microalgal cells showed tolerance to antibiotics, PRM, without significant cell growth inhibition, chlorophyll reduction, and paramylon and lipid alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of UV radiation on photosynthetic organisms has been extensively investigated over the past decades due to the depletion of ozone layer. Many studies have analyzed the effect on UV radiation on photosynthetic organisms and observed that UV radiation causes serious damages to photosynthetic apparatus thus, induced a decrease of the photosynthetic capacity (Prasad and Zeeshan (2004), Holzinger and Lutz (2005) and Takahashi et al (2006)). …”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of the AR has been shown to increase with the dose of radiation up to a certain threshold (Bryant, 1976). A specific dose of UVB was required to induce AR in Euglena (Takahashi et al, 2006). Induction of AR by methylating agents has been reported in eukaryotic cells as well.…”
Section: Molecular Mechanisms Of the Adaptive Responsementioning
confidence: 98%
“…It has been proposed that these effects could be related to the induction of an AR. The AR induced by conditioning UVB exposures in Euglena may not be due to biosynthetic UV-absorbing compounds, but to the induction of photolyase enzymes (Takahashi et al, 2006). Activation of UVB-induced AR in human skin cells could involve a p53-dependent gene program with p53-induced cell cycle arrest and DNA repair (Decraene et al, 2005).…”
Section: Sakamoto-hojomentioning
confidence: 99%